Refocusing democracy: the Chinese government's framing strategy in political language. Issue 2 (17th February 2020) - Hu, Yue
ABSTRACT: Authoritarian governments talk about democracy frequently. Why do they do so? What does the term democracy mean in an authoritarian political language? This research uses a computer-assisted text analytical approach illustrating how an authoritarian government strategically manipulates the discourse about democracy to benefit itself. By analysing over a million political articles published in People's Daily over five decades, the study shows a refocusing framing strategy, in which the Chinese government defines democracy not with regime justification but with national policy priorities while denoting democracy most frequently alongside the fundamental values. With this strategy, the framed discourse appear to be consistent with the fundamental values in Western democracies but work for the preservation of the authoritarian regime.